Modification of solar driven TiO2 photocatalyst via doped and co doped methods for degradation of methylene blue / ‘Aizat Azhari Mohd Yatim - 'Aizat Azhari, Mohd Yatim (2017)
The presence of vanadium (V) and nitrogen (N) in titanium dioxide (TiO2) nanoparticles enhanced its photocatalytic activity against degradation methylene blue (MB). Vanadium nitrogen co-doped TiO2 (VN co-doped TiO2) photocatalyst is synthesised by the modified sol–gel method. The corresponding samples for V doped TiO2 (0.006 %, 0.125 %, 0.250 %, 0.500 %, 1.000 %) were labelled as V1 doped TiO2, V2 doped TiO2, V3 doped TiO2, V4 doped TiO2, and V5 doped TiO2 while for N doped TiO2 (0.100 %, 0.250 %, 0.500 %, 0.750 %, 1.000 %) were labelled as N1 doped TiO2, N2 doped TiO2, N3 doped TiO2, N4 doped TiO2, and N5 doped TiO2. The subsequent photocatalysts were characterised using X-ray Diffraction (XRD), Brunauer-Emmet-Teller (BET), Raman Spectroscopy, UV–Vis Diffuse Reflectance Spectroscopy (DRS), Field Emission Scanning Electron Microscope (FESEM), Energy Dispersive X-ray (EDX) and X-ray Photoelectron Spectroscopy (XPS). The VN co-doped TiO2 photocatalyst reported a narrower band gap (2.65 eV) compared to a single-doped V doped TiO2 (2.89 eV), N doped TiO2 (2.87 eV), and undoped TiO2 (3.18 eV). Moreover, VN co-doped TiO2 photocatalyst also demonstrated superior photocatalytic activity for the degradation of MB compared to the undoped and single-doped TiO2 with almost 99 % of MB degradation in 120 minutes. The incorporation of V and N in the TiO2 lattice resulted in isolated energy levels near the valence and conduction bands, which considerably narrowed the band gap. Furthermore, the recombination between photogenerated charges was reduced due to the low concentrations of dopants, since these energy levels can also trap photoexcited holes and electrons. The synergistic effects between V and N in TiO2 increased the photocatalytic activity of VN co-doped TiO2 nanoparticles.